Customs Union, Tariff Reform and Trade in Differentiated Products. - Venables, A (CEPR, 1985)
The paper analyses tax and tariff policy for trade between economies which each contain a monopolistically competitive industry producing differentiated products. The consequences of tax changes by a single country are examined, and the general desirability of taxing imports more heavily than domestically produced goods is established. Customs union theory is analysed by studying coordinated tax changes by a group of countries; circumstances under which customs union formation and enlargement will benefit members are found. Game theoretic techniques are used to investigate which countries will coalesce into a customs union.